The Relationship Between Sensorimotor Integration and Social Processing - Howard, Ellen M. (2023)
To interact with the physical world, the brain must integrate information across multiple sensory and motor domains to create a stable representation of the body. Crucially, it is the effective integration of visual, tactile, proprioceptive, and motor information which creates the experience of a bodily self. The embodied cognition framework proposes that important social processes such as self-awareness, perspective-taking, and interpersonal synchrony are grounded within the bodily self. Thus, exploring the links between the senses, the body, and social processes can elucidate how humans interact, understand each other, and move in time with each other. Research investigating why certain populations show differences in how they socially interact can shed further light on the contribution of sensorimotor integration in social processing. Autism is a neurodevelopmental disorder characterised by differences in social interaction, communication, and sensory processing. Research suggests that sensory processing differences may account for the characteristic differences in social behaviour in autism. However, the exact relationship between sensorimotor integration and social processing is not fully understood.